Glycine and L-Arginine supplementation ameliorates gastro-duodenal toxicity in a rat model of NSAID (Diclofenac)-gastroenteropathy via inhibition of oxidative stress (2021)
Objectives: This study examined the possible protective roles of exogenous glycine (Gly) and L-Arginine (L-Arg) against Diclofenac (DIC)-induced gastro-duodenal damage in rats. Methods: Rats were divided into Group A (control), Group B (DIC group) and Groups C–F which were pre-treated for five days with Gly1 (250 mg/kg), Gly2 (500 mg/kg), L-Arg1 (200 mg/kg) and L-Arg2 (400 mg/kg), respectively, before co-treatment with DIC for another three days. Hematologi cal, biochemical and histopathological analyses were then carried out. Results: DIC produced significant (p<0.05) reduction in PCV (13.82%), Hb (46.58%), RBC (30.53%), serum total protein (32.72%), albumin (28.44%) and globulin (38.01%) along with significant (p<0.05) elevation of serum MPO activity (83.30%), when compared with control. In addition, DIC increased gastric H2O2 and MDA levels by 33.93 and 48.59%, respectively, while the duodenal levels of the same parameters increased by 19.43 and 85.56%, respectively. Moreover, SOD, GPx and GST activities in the DIC group were significantly (p<0.05) reduced in the stomach (21.12, 24.35 and 51.28%, respectively) and duodenum (30.59, 16.35 and 37.90%, respectively), compared to control. Treatment with Gly and L-Arg resulted in significant amelioration of the DIC-induced alterations although L-Arg produced better amelioration of RBC (29.78%), total protein (10.12%), albumin (9.93%) and MPO (65.01%), compared to the DIC group. The protective effects of both amino acids against oxidative stress parameters and histological lesions were largely similar. Conclusions: The data from this study suggest that Gly or L-Arg prevented DIC-induced gastro-duodenal toxicity and might, therefore be useful in improving the therapeutic index of DIC.